The whipworm (Trichuris suis) secretes prostaglandin E2 to suppress proinflammatory properties in human dendritic cells. Issue 2 (2nd November 2016) - Laan, Lisa C.; Williams, Andrew R.; Stavenhagen, Kathrin; Giera, Martin; Kooij, Gijs; Vlasakov, Iliyan; Kalay, Hakan; Kringel, Helene; Nejsum, Peter; Thamsborg, Stig M.; Wuhrer, Manfred; Dijkstra, Christine D.; et al.
ABSTRACT: Clinical trials have shown that administration of the nematode Trichuris suis can be beneficial in treating various immune disorders. To provide insight into the mechanisms by which this worm suppresses inflammatory responses, an active component was purified from T. suis soluble products (TsSPs) that suppress TNF and IL‐12 secretion from LPS‐activated human dendritic cells (DCs). Analysis by liquid chromatography tandem mass spectrometry identified this compound as prostaglandin (PG)E2. The purified compound showed similar properties compared with TsSPs and commercial PGE2 in modulating LPS‐induced expression of many cytokines and chemokines and in modulating Rab7B and P2RX7 expression in human DCs. Furthermore, the TsSP‐induced reduction of TNF secretion from DCs is reversed by receptor antagonists for EP2 and EP4, indicating PGE2 action. T. suis secretes extremely high amounts of PGE2 (45–90 ng/mg protein) within their excretory/secretory products but few related lipid mediators as established by metabololipidomic analysis. Culture of T. suis with several cyclooxygenase (COX) inhibitors that inhibit mammalian prostaglandin synthesis affected the worm's motility but did not inhibit PGE2 secretion, suggesting that the worms can synthesize PGE2 via a COX‐independent pathway. We conclude that T. suis secretes PGE2 to suppress proinflammatory responses in human DCs, thereby modulating the host's immune response.—Laan, L. C., Williams, A. R., Stavenhagen, K., Giera, M., Kooij, G., Vlasakov, I., Kalay, H., Kringel, H., Nejsum, P., Thamsborg, S. M., Wuhrer, M., Dijkstra, C. D., Cummings, R. D., van Die, I. The whipworm (Trichuris suis) secretes prostaglandin E2 to suppress proinflammatory properties in human dendritic cells. FASEB J. 31, 719–731 (2017). http://www.fasebj.org